Analisis Pengaruh Pembiayaan Surat Berharga Negara (SBN) Terhadap Tingkat Kemiskinan Indonesia: Masa Normal Dan Masa Pandemi Covid-19 (2020-2023) - Greace Havana Tamba; Tarigan, Gideon; Simanjuntak, Hendra Inbowo; Br Siahaan, Viona Tasya; Hamonangan Siallagan; Christnova Hasugian (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
When the country is experiencing a fiscal deficit, especially during a crisis, the issuance of government bonds is considered a necessity, predominantly to finance productive sectors. This paper aims to analyze the effect of financing originating from Government Bonds (SBN) on poverty levels in Indonesia. The analysis is carried out over a period from normal times (2012- 2019) to the Covid-19 pandemic crisis (2020-2022). The method of this study is explanatory research through a quantitative approach and multiple linear regression in this study using SPSS 25. The findings from this study are that there has been an increase in SBN and government allocation on social assistance spending. Generally, social assistance policies have also proven effective in reducing the percentage of poverty in the entire community, especially rural communities, yet have not been able to reduce urban poverty. Meanwhile, at the time of Covid 19 Pandemic, the increase of SBN cannot automatically eradicate poverty, as the social assistance budget does not have a significant effect on the percentage of poverty in urban areas.